Comparison of sniffing position and simple head extension for visualization of glottis during direct laryngoscopy. - Bhattarai, B; Shrestha, S K; Kandel, S (Kathmandu University Medical Journal, 2012)
Background The ability of good glottis visualization during direct laryngoscopy is major determinant of easy tracheal intubation. Sniffing position for laryngoscopy is considered as gold standard and ideal position. Several studies have questioned the validation of sniffing potion. Objectives This study aims to compare relative efficacy of sniffing position and simple head extension for visualization of glottis during direct laryngoscopy. Methods Four hundred patients undergoing elective surgery under general anesthesia requiring endotracheal intubation were randomized into two groups and study was concluded. Glottic visualization was assessed using modified Cormack and Lehane classification. After laryngoscopy, tracheal intubation was performed and intubation difficulty scale was noted. Results Both the groups were comparable regarding glottis visualization. Both the groups were comparable in demographic profiles. All the intubation difficulty scale variables were comparable in both the groups except N3. Total Intubation Difficulty Score was better in sniffing position than in simple head extension group. Conclusion Glottic visualization and intubation difficulty score was better in sniffing position as compared to simple head extension. http://dx.doi.org/10.3126/kumj.v9i1.6265 Kathmandu Univ Med J 2011;9(1):58-63